Structurally-phase transformations at contact fusion of pair aluminium-nickel - Panichkin, A.V.; Aubakirova R.К.; Alpysbay I.М.; Zhumakanova, V.R. (Recent Contributions to Physics, 2012)
Thermodifusion interraction of firm nickel and liquid aluminium was investigated at various modes of processing. For first time it is established that NiAl intermetallic phase existing in the wide concentration range is formed in the diffusion zone in the form of two layers of NiAl(1) and NiAl(2) which correspond to the composition of the extreme regions of the compound on the phase diagram which indicates the gap in solubility in the system.